The Effect of Child Care Costs on Married Women's Labor Force Participation - Connelly, Rachel (The Review of Economics and Statistics, 1992)
The effect of child-care costs on the probability that married women with children will participate in the labor market is examined. Child-care costs are estimated.using a generalized Tobit specification corrected for selection. Estimates of a structural probit model of labor-force participation provide evidence to support the prediction that increased child-care costs lower the probability of participation. It is also shown that the lower rate of labor-force participation among mothers of preschoolers is entirely the result of the higher child-care costs faced by these women and endogeneity of the number of young children in the participation equation. Copyright 1992 by MIT Press.